Serum Amyloid A Is a Biomarker of Disease Activity and Health-Related Quality-of-Life in Patients with Antineutrophil Cytoplasmic Antibody-Associated Vasculitis. (16th December 2020) - Yoon, Taejun; Ahn, Sung Soo; Yoo, Juyoung; Song, Jason Jungsik; Park, Yong-Beom; Lee, Sang-Won
Abstract : Serum amyloid A (SAA) is one of the acute phase proteins synthesized in hepatocytes and secreted by various inflammation or infectious stimuli. We investigated the clinical implication of measuring SAA in patients with antineutrophil cytoplasmic antibody- (ANCA-) associated vasculitis (AAV). Seventy-five patients who had been classified as AAV and enrolled in our prospective observational cohort for AAV patients were included. Clinical and laboratory data were obtained on the day of blood sampling, and SAA was measured by ELISA kits. Birmingham Vasculitis Activity Score (BVAS) and Short-Form 36-Item Health Survey (SF-36) were assessed for disease activity and health-related quality-of-life (HRQoL) measures. We stratified patients into having high BVAS when the BVAS was over the median values, and those with either low SF-36 PCS or low SF-36 MCS were defined as having poor HRQoL. Multivariate logistic regression analysis was conducted to estimate independent predictors of high BVAS. The relative risk (RR) was analyzed using the contingency tables and the chi-squared test. SAA was positively correlated with BVAS (r = 0.642 ) and FFS (r = 0.367 ) and was inversely correlated with both the SF-36 physical component summary (r = − 0.456 ) and mental component summary scores (r = − 0.394 ). Furthermore, SAA was significantly correlated with acute phase reactants ESR (r = 0.611 ) and CRP (r = 0.629 ). Patients with high BVAS exhibited significantly higher SAA than those with low BVAS (1317.1 ng/mL vs. 423.1 ng/mL). In multivariable logistic regression analysis, serum albumin (odds ratio (OR) 0.132) and SAA > 1173.6   ng / mL (OR 15.132) were independently associated with high BVAS. The risk of having high BVAS and poor HRQoL in patients with SAA > 1173.6   ng / mL was higher than in those with SAA ≤ 1173.6   ng / mL (RR 3.419 and 1.493). Our results suggest that SAA might be a useful biomarker in assessing disease activity and HRQoL in AAV.